2018
DOI: 10.1002/1878-0261.12381
|View full text |Cite
|
Sign up to set email alerts
|

A pan‐cancer atlas of cancer hallmark‐associated candidate driver lncRNAs

Abstract: Substantial cancer genome sequencing efforts have discovered many important driver genes contributing to tumorigenesis. However, very little is known about the genetic alterations of long non‐coding RNAs (lncRNAs) in cancer. Thus, there is a need for systematic surveys of driver lncRNAs. Through integrative analysis of 5918 tumors across 11 cancer types, we revealed that lncRNAs have undergone dramatic genomic alterations, many of which are mutually exclusive with well‐known cancer genes. Using the hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 110 publications
0
16
0
Order By: Relevance
“…In a previous study, Bing et al, (2017) identified several lncRNAs altered at genomics level in lung cancer. LINC00885 gene amplification was among the highly altered lncRNAs in 38% of lung squamous cell carcinomas [ 18 ]. More recently, Deng et al (2018) identified 378 candidate driver lncRNAs through integrative analysis of CNA data obtained from TCGA Pan-Cancer dataset [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, Bing et al, (2017) identified several lncRNAs altered at genomics level in lung cancer. LINC00885 gene amplification was among the highly altered lncRNAs in 38% of lung squamous cell carcinomas [ 18 ]. More recently, Deng et al (2018) identified 378 candidate driver lncRNAs through integrative analysis of CNA data obtained from TCGA Pan-Cancer dataset [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“… 2 The prevalent focal and arm-level SCNAs affected large cancer genome regions that not only included protein-coding genes (PGs) but also non-coding regions. 3 , 4 How to elucidate the functional roles of SCNAs in cancers and how these SCNAs disorder cellular homeostasis and further promote cancer progression are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among DEGs, we focused on genes involved in reprogramming energy metabolism as well as genes related to malignant tissue development. The reprogramming energy metabolism-related genes were identified by hallmark-associated GO terms in our previous research ( Deng et al, 2018 ). Then, we performed the univariable Cox regression analysis to select genes associated with overall survival in the training cohort.…”
Section: Methodsmentioning
confidence: 99%